2016
DOI: 10.1186/s12957-016-0801-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of axillary exclusion on seroma formation after modified radical mastectomy

Abstract: BackgroundBreast cancer represented 35.1 % of total female cancer cases in Egypt. Seroma is one of the most serious and common complications of mastectomy and axillary dissection with incidence between 15 and 81 %. Seroma formation delays wound healing and increases susceptibility to infection, skin flap necrosis, and persistent pain as well as prolonging convalescence. Therefore, several techniques have been investigated to minimize seroma formation with no consistent success. Axillary exclusion is a techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…90% was in the control group and 42.5% in the study group with a reduction of about 65%. and in another study published by Faisal M, et al at (2016) [23] on 64 patients also they found significant reduction in seroma formation as well as time of drain removal after they have used similar technique (p < 0.01).…”
Section: Discussionmentioning
confidence: 70%
“…90% was in the control group and 42.5% in the study group with a reduction of about 65%. and in another study published by Faisal M, et al at (2016) [23] on 64 patients also they found significant reduction in seroma formation as well as time of drain removal after they have used similar technique (p < 0.01).…”
Section: Discussionmentioning
confidence: 70%
“…Seroma is a prevalent and annoying problem post breast and lymph nodes removal leading to the majority of complications that happens, for instance, wound infection, skin flap necrosis, wound dehiscence, and lymphedema. Because of the potentially severe effects of seroma, several approaches have been described to obliterate the dead space aiming at reduction of seroma formation; for example, using compression bandage, suction drains, flap fixation with sutures, utilization of ultrasound scalpel or laser scalpel in dissection, sclerotherapy, immobilization from the affected arm, topical use of tranexamic acid and fibrin glue application [ [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Axillary exclusion is a procedure devised to obliterate dead space thereby excluding axilla from the rest of wound after axillary clearance and leading to minimize collection. 9 In this technique we apply continuous stitches with vicryl 2/0 between the mastectomy skin flap and the lateral margin of pectoralis major, and place few interrupted sutures between www.apmcfmu.com pectoralis major and minor and the flap to separate the axillary space from the rest of the mastectomy wound and obliterate the dead space so created after axillary clearance. A pressure dressing is applied over axilla and also the mastectomy wound.…”
Section: Introductionmentioning
confidence: 99%